2011
DOI: 10.1590/s1517-83822011000200002
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of Propionibacterium acnes in lesional and non-lesional skin of patients with progressive macular hypomelanosis by real-time polymerase chain reaction

Abstract: Little is known about the etiology of progressive macular hypomelanosis, although it has been suggested that Propionibacterium acnes plays an important role. While microbiological culture is commonly employed to identify Propionibacterium acnes, new identification methods have been under investigation, amongst them polymerase chain reaction. To determine the cut-off point for the number of genome copies of Propionibacterium acnes in the lesional skin of patients with progressive macular hypomelanosis as a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
1
0
4
Order By: Relevance
“… 6 Quantities of P. acnes have been shown to be elevated in lesional skin of patients with PMH through both culture and quantitative real-time PCR. 5 PMH diagnosis continues to elude practitioners, and studies have yet to suggest a standard approach. A recent case study suggested that the use of Wood’s lamp examination can aid diagnosis by revealing a specific follicular pattern of fluorescence, proportional to the concentration of P. acnes , that is not present in hypopigmented lesions caused by other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Quantities of P. acnes have been shown to be elevated in lesional skin of patients with PMH through both culture and quantitative real-time PCR. 5 PMH diagnosis continues to elude practitioners, and studies have yet to suggest a standard approach. A recent case study suggested that the use of Wood’s lamp examination can aid diagnosis by revealing a specific follicular pattern of fluorescence, proportional to the concentration of P. acnes , that is not present in hypopigmented lesions caused by other etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto aos achados histofisiopatológicos, sete estudos [12][13][14][16][17][19][20] relataram sobre o uso de técnicas histopatológicas para investigação diagnóstica da doença. Sendo que Relyveld e colaboradores 13 também verificaram a ausência de esporos e micélios no exame histológico, esta verificação também foi utilizada por mais quatro estudos 14,[16][17]20 com o objetivo de excluir possíveis diagnósticos diferenciais Acerca dos achados histopatológicos quatro estudos mencionaram a diminuição da melanina epidérmica 5,[12][13]17 . Relyveld e colaboradores 13 , através da microscopia eletrônica, também relataram a presença de melanossomas menores e menos melanizados na pele lesionada de todos os oito pacientes.…”
Section: Categoria Iii: Diagnóstico Para Hmpunclassified
“…Levando em consideração esses aspectos, dois estudos 5,16 24,26 , um com a fototerapia UVB NB 17 (UVB de banda estreita) e um com fototerapia UVB 19 e três com clindamicina a 1% 12,15,18 . Dois mencionaram o uso da minociclina 14,21 de forma isolada e em um 18 a minociclina foi associada ao uso tópico de clindamicina, contudo foi substituída pelo peróxido de benzoíla.…”
Section: Categoria Iii: Diagnóstico Para Hmpunclassified
See 2 more Smart Citations